Реліктові типи намогильних знаків з середньої Наддніпрянщини - Товкайло, М. (Народна творчість та етнографія, 2006)
This article is the continuation of the research of the tomb signs, their types and peculiarities. The symbol of the cross bearing both pagan and Christian meaning was a wide-spread tomb sign since early Middle Ages. It connects Christian symbol of Christ's triumph and pagan world tree, the symbol of the Great Goddess. Crosses having anthropomorphic features are depicted in the article as well.